Multi-layer biodegradable film
A multilayer film with biodegradable polyester and polymer layers addresses the challenge of balancing mechanical, biodegradability, and optical transparency in packaging films, offering superior performance in elasticity, biodegradability, and transparency.
Patent Information
- Application Number
- JP2024177280
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-06-13
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2037-06-13
AI Technical Summary
Existing biodegradable packaging films face challenges in balancing high mechanical properties, biodegradability, and optical transparency, often compromising on one or more of these characteristics.
A multilayer film comprising at least one biodegradable aliphatic and/or aliphatic-aromatic polyester layer A and a polymer layer B, which includes components like polyhydroxyalkanoate and starch, achieving a combination of high modulus of elasticity, biodegradability, and optical transparency.
The multilayer film exhibits excellent mechanical properties, rapid biodegradability under composting conditions, and high optical transparency, making it suitable for various packaging applications.
Smart Images

Figure 2025004185000001
Abstract
Description
[Technical field]
[0001] Description The present invention relates to a multilayer biodegradable film, in particular suitable for use in the manufacture of various types of packaging, in particular in bags for carrying goods and bags for food packaging, such as bags for fruits and vegetables. In addition to having high levels of mechanical properties, in particular a high modulus of elasticity, said film also has the property of considerable light transmission. [Background technology]
[0002] The manufacture of packaging, in particular bags for packaging food products, such as bags for fruits and vegetables, requires the use of films that combine good mechanical properties with other properties that are positive for the consumer, such as light-transmitting properties that allow the consumer to use the packaging, in particular by viewing the object contained inside from the outside. Summary of the Invention [Problem to be solved by the invention]
[0003] In the biodegradable packaging sector, in addition to mechanical and optical issues, there is also the need to utilize materials that, when they reach the end of their primary use, can decompose without accumulating waste in the environment. The development of a biodegradable film combining these different properties is in fact a challenge that requires the balancing of different needs, which are often very contradictory to each other. In fact, certain criteria for mechanical properties and biodegradability can be achieved by utilizing a composition of materials that share each of the final properties of the film according to their different properties, but the achievement of high light transmission properties is very often hindered by the heterogeneous properties of said compositions. For manufacturers of biodegradable packaging films, this means that they must decide whether to use films with a high level of mechanical and biodegradable properties as well as non-optimal light transmission properties, or, conversely, to utilize aspects that are linked to the optical properties of the packaging, thereby accepting a poorer performance in terms of mechanical and biodegradable properties.
[0004] Therefore, if it were possible to develop a film capable of balancing these contrasting requirements and thus characterized by a high level of biodegradability and mechanical properties, in particular a high modulus, and by the properties of considerable light transparency, this would make it possible to overcome the current problems mentioned above. [Means for solving the problem]
[0005] The present invention addresses this problem and provides a solution that allows to properly balance these different requirements. In particular, the present invention relates to a multilayer film comprising at least one first layer A and at least one second layer B, wherein said layers A and B are different from each other, and layer A is biodegradable. aliphatic and / or aliphatic-aromatic polyesters or polyvinyl alcohol or copolymers thereof, And Tier B: i) 30-95% by weight, preferably 50-85% by weight, relative to the total of component iv, of at least one polyester comprising a) and b) of: a) Based on the total dicarboxylic acid content: a1) 35-70 mol %, preferably 40-60 mol %, more preferably 45-60 mol % of units derived from at least one aromatic dicarboxylic acid; a2) 65-30 mol %, preferably 60-40 mol %, more preferably 55-40 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; a3) 0-5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid; A dicarboxylic acid component comprising: b) For the total diol content: b1) 95-100 mol % of units derived from at least one saturated aliphatic diol; b2) 0-5 mol % of units derived from at least one unsaturated aliphatic diol; A diol component comprising: ii) 0.1-50% by weight, preferably 5-40% by weight, of at least one polymer of natural origin relative to the total of component iv; iii) 1-40% by weight, preferably 2-30% by weight, of at least one polyhydroxyalkanoate, based on the total of components iv; iv) 0-15% by weight, based on the total of components iv, of at least one inorganic filler; v) 0-5% by weight, preferably 0-0.5% by weight, based on the total of component iv, of at least one crosslinker and / or chain extender comprising at least one compound having two and / or more functional groups containing isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxide, anhydride or divinyl ether groups and mixtures thereof. Includes.
[0006] One particular property of the multilayer film according to the invention is that its layer structure comprises at least one layer (layer A) comprising an aliphatic-aromatic and / or aliphatic biodegradable polyester or polyvinyl alcohol or copolymers thereof, and at least one layer (layer B) comprising a polymer composition comprising component iv. Surprisingly, it has been found that a multilayer film with this combination of substances has very good mechanical, biodegradable and optical properties, which makes it suitable for producing various kinds of packaging. In particular, layer B of the multilayer film according to the invention comprises in its structure continuous and dispersing layers capable of giving the film rapid biodegradability under industrial composting conditions and more preferably in home composting according to the UNI 11355 standard. The film also has a high level of mechanical properties and is extremely thin; if, for example, in the form of a bag with a height of less than 50 cm and a width of less than 40 cm (with or without gussets) and in this case the bag has a handle with a handle width between 5 and 3 cm and a thickness of less than 15 μm and more preferably less than 12 μm, the bag is capable of supporting a weight of at least 3 kg, even more preferably at least 4 kg under the conditions of a jogging test. By way of example, one type of manual jogging test would be considered as lifting a bag 40 cm off the ground 10 times in succession without any tearing. Although the structure of each individual layer B has optical properties significantly worse than those of non-biodegradable materials commonly used in the production of packaging, such as HDPE, the multilayer film according to the invention has optical properties similar to those of HDPE due to its structure, a structure that provides a combination of at least one layer A and at least one layer B, while at the same time maintaining the biodegradable properties of layer B (industrial composting and more preferably home composting ability and / or dispersibility in mechanical mixing processes preceding treatments involving anaerobiosis). In particular, the multilayer film has an optical transmission of 90% or more, preferably 91% or more, a haze of 65% or less, preferably 55% or less, and a transparency of 20% or more, preferably 40% or more.
[0007] The invention relates to various kinds of packaging, in particular bags for the transport of goods and food packaging, e.g. bags for food and vegetables, comprising said multilayer film.
[0008] The multilayer film according to the invention comprises at least one layer A and at least one layer B, preferably characterized by a mutual arrangement selected from A / B and A / B / A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Layer A As far as layer A is concerned, it comprises at least one aliphatic and / or aliphatic-aromatic polyester or polyvinyl alcohol or copolymers thereof. In the case of an aliphatic-aromatic polyester, it preferably comprises c) and d): c) for the total dicarboxylic acid components: c1) 35-70 mol %, preferably 40-60 mol %, more preferably 45-60 mol % of units derived from at least one aromatic dicarboxylic acid; c2) 65-30 mol %, preferably 60-40 mol %, more preferably 55-40 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; c3) 0-5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid; A dicarboxylic acid component comprising: d) For the total diol content: d1) 95-100 mol % of units derived from at least one saturated aliphatic diol: d2) 0-5 mol % of at least one unsaturated aliphatic diol-derived unit A diol component comprising:
[0010] The aromatic dicarboxylic acid in component c1 is preferably selected from aromatic dicarboxylic acids of the phthalic acid type, preferably terephthalic acid or isophthalic acid, more preferably terephthalic acid and heterocyclic dicarboxylic aromatic compounds, preferably 2,5-furandicarboxylic acid, 2,4-furandicarboxylic acid, 2,3-furandicarboxylic acid, 3,4-furandicarboxylic acid, more preferably 2,5-furandicarboxylic acid, esters, salts and mixtures thereof. Preferred embodiments of said aromatic dicarboxylic acids are: from 1 to 99 mol %, preferably from 5 to 95 mol %, and more preferably from 10 to 80 mol % of terephthalic acid, its esters or salts; - 99 to 1 mol %, preferably 95 to 5 mol %, and more preferably 90 to 20 mol % of 2,5-furandicarboxylic acid, its esters or salts Includes.
[0011] The saturated aliphatic dicarboxylic acid in component c2 is preferably a saturated C2-C 24 , preferably C4-C 13 , more preferably C4-C 11 and the dicarboxylic acids C1-C 24 , preferably C1-C4, alkyl esters, salts thereof and mixtures thereof. Preferably, the saturated aliphatic dicarboxylic acid is selected from succinic acid, 2-ethylsuccinic acid, glutaric acid, 2-methylglutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecane diacid, dodecane diacid, brassylic acid, hexadecanedioic acid, octadecanedioic acid and their C 1-24 In a preferred embodiment of the present invention, the saturated aliphatic dicarboxylic acid is selected from succinic acid, adipic acid, azelaic acid, sebacic acid, brassylic acid, C1-C alkyl esters thereof, at least 50 mol %, preferably 60 mol % or more, more preferably 65 mol % or more. 24 , preferably C1-C4, esters and mixtures thereof. In a preferred embodiment, the mixture comprises or consists of adipic acid and azelaic acid, the azelaic acid being present in an amount between 5 and 40 mol %, more preferably between 10 and 35 mol %, based on the sum of adipic acid and azelaic acid.
[0012] The unsaturated aliphatic dicarboxylic acids in component c3 are preferably itaconic acid, fumaric acid, 4-methylene-pimelic acid, 3,4-bis(methylene)nonanedioic acid, 5-methylene-nonanedioic acid, their C1-C 24 In a preferred embodiment of the present invention, the unsaturated aliphatic dicarboxylic acid is selected from at least 50 mol %, more preferably more than 60 mol %, more preferably more than 65 mol % of itaconic acid and its C1-C4 alkyl esters, salts thereof and mixtures thereof. 24 , preferably C1-C4, and mixtures including esters. More preferably, the unsaturated aliphatic dicarboxylic acid comprises itaconic acid.
[0013] As far as the saturated aliphatic diols in component d1 are concerned, these are preferably selected from 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,4-cyclohaxane dimethanol, neopentyl glycol, 2-methyl-1,3-propanediol, dianhydrosorbitol, dianhydromannitol, dianhydroiditol, cyclohexanediol, cyclohexanemethanediol, dialkylene glycols and polyalkylene glycols having a molecular weight of 100-4000, such as polyethylene glycol, polypropylene glycol, etc., and mixtures thereof. A preferred diol component comprises at least 50 mol % of one or more diols selected from 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, and more preferably the diol component comprises or consists of 1,4-butanediol.
[0014] As far as the unsaturated fatty acid diols in the d2 component are concerned, these are preferably selected from cis 2-butene-1,4-diol, trans 2-butene-1,4-diol, 2-butyne-1,4-diol, cis 2-pentene-1,5-diol, trans 2-pentene-1,5-diol, 2-pentyne-1,5-diol, cis 2-hexene-1,6-diol, trans 2-hexene-1,6-diol, 2-hexyne-1,6-diol, cis 3-hexene-1,6-diol, trans 3-hexene-1,6-diol, 3-hexyne-1,6-diol.
[0015] In the case of aliphatic polyesters, this preferably comprises e) and f): e) For the total dicarboxylate content: e1) 95-100 mol % of units derived from at least one aliphatic dicarboxylic acid; e2) 0-5 mol % of units derived from at least one unsaturated fatty acid dicarboxylic acid; A dicarboxyl component comprising; f) For the total diol content: f1) 95-100 mol % of units derived from at least one saturated aliphatic diol; f2) 0-5 mol % of units derived from at least one unsaturated aliphatic diol; A diol component comprising:
[0016] The saturated aliphatic dicarboxylic acid in component e1 is preferably a saturated C2-C 24 , preferably C4-C 13 , more preferably C4-C 11 Dicarboxylic acids of C 1- C 24 , preferably C1-C4, alkyl esters, salts thereof and mixtures thereof. Preferably, the saturated aliphatic dicarboxylic acid is selected from succinic acid, 2-ethylsuccinic acid, glutaric acid, 2-methylglutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecane diacid, dodecane diacid, brassylic acid, hexadecanedioic acid, octadecanedioic acid and their C 1-24 It is selected from alkyl esters.
[0017] The unsaturated aliphatic dicarboxylic acids in component e2 are preferably itaconic acid, fumaric acid, 4-methylene-pimelic acid, 3,4-bis(methylene)nonanedioic acid, 5-methylene-nonanedioic acid, their C1-C 24 In a preferred embodiment of the present invention, the unsaturated fatty acid dicarboxylic acid is selected from at least 50 mol %, preferably more than 60 mol %, more preferably more than 65 mol % of itaconic acid and its C1-C4 alkyl esters, salts thereof and mixtures thereof. 24 , preferably C1-C4, and mixtures including esters. More preferably, the unsaturated aliphatic dicarboxylic acid comprises itaconic acid.
[0018] As far as the saturated aliphatic diols in component f1 are concerned, these are preferably selected from 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1.5-pentanediol, 1,6-hexanediol, 1.7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, 2-methyl-1,3-propanediol, dianhydrosorbitol, dianhydromannitol, dianhydroiditol, cyclohexanediol, cyclohexanemethanediol, dialkylene glycols and polyalkylene glycols having a molecular weight of 100-4000, such as polyethylene glycol, polypropylene glycol, etc., and mixtures thereof. Preferably, the diol component comprises at least 50 mole % of one or more diols selected from 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, and more preferably, the diol component comprises or consists of 1,4-butanediol.
[0019] As far as the unsaturated aliphatic diols in component f2 are concerned, these are preferably selected from cis 2-butene-1,4-diol, trans 2-butene-1,4-diol, 2-butyne-1,4-diol, cis 2-pentene-1,5-diol, trans 2-pentene-1,5-diol, 2-pentyne-1,5-diol, cis 2-hexene-1,6-diol, trans 2-hexene-1,6-diol, 2-hexyne-1,6-diol, cis 3-hexene-1,6-diol, trans 3-hexene-1,6-diol, 3-hexyne-1,6-diol.
[0020] The Mn molecular weight of said aliphatic and / or aliphatic-aromatic polyesters in layer A is preferably ≧20000, more preferably ≧40000. As far as the polydispersity index of the molecular weights, Mw / Mn, is concerned, this is instead preferably between 1.5 and 10, more preferably between 1.6 and 5, even more preferably between 1.8 and 2.7. The Mn and Mw molecular weights can be measured using Gel Permeation Chromatography (GPC). The determination can be performed using a chromatographic system maintained at 40° C., a set of two columns in series (particle sizes 5 μm and 3 μm with mixed porosity), a refractive index detector, chloroform as eluent (flow rate 0.5 ml / min), and polystyrene as reference standard.
[0021] The terminal acid group content of the aliphatic and / or aliphatic-aromatic polyester in Layer A is preferably less than 100 meq / kg, preferably less than 60 meq / kg, and more preferably less than 40 meq / kg. The acid end group content can be determined as follows: 1.5-3 g of polyester is placed in a 100 ml flask with 60 ml of chloroform. After the polyester is completely dissolved, 25 ml of 2-propanol is added, and then 1 ml of deionized water is added immediately before analysis. The solution so obtained is titrated against a prestandardized NaOH solution in ethanol. A suitable indicator is used to determine the end point of the titration, such as a glass electrode for acid-base titrations in non-aqueous solvents. The acid end group content is calculated based on the consumption of NaOH solution in ethanol according to the following formula: Terminal acid group content (meq / kg polymer) = [(V eq -V b )·T]·1000 / P Where: eq = ml of NaOH in ethanol at the end point of titration of sample; V b = ml of NaOH solution in ethanol required to reach pH 9.5 during the blank titration; T=concentration of NaOH solution in ethanol expressed as moles / litre; P = weight of sample in grams It is calculated using:
[0022] Preferably, the aliphatic and / or aliphatic-aromatic polyesters in Layer A have an inherent viscosity of 0.3 dl / g or more (measured using an Ubbelohde viscometer for a solution of 0.2 g / dl concentration in CHCl3 at 25°C), preferably between 0.3 and 2 dl / g, more preferably between 0.4 and 1.1 dl / g.
[0023] Said aliphatic and / or aliphatic-aromatic polyesters in layer A are biodegradable. By biodegradable polymers the present invention means biodegradable polymers according to standard EN13432.
[0024] Said aliphatic and / or aliphatic-aromatic polyesters in layer A may be synthesised by any method known in the art, in particular, advantageously by means of a polycondensation reaction.
[0025] Advantageously, the synthesis process may be carried out in the presence of a suitable catalyst, such as organometallic, for example stannic acid derivatives of tin, titanium compounds, for example orthobutyl titanate, aluminum compounds, for example triisopropylaluminum, antimony and zinc and zirconium compounds and mixtures thereof.
[0026] In another embodiment of the invention, said aliphatic polyester in layer A is a polyester of a hydroxy acid, preferably poly-ε-caprolactone. Said at least one aliphatic and / or aliphatic-aromatic polyester in layer A is advantageously mixed with one or more other components, in which case layer A comprises a composition comprising at least one aliphatic and / or aliphatic-aromatic polyester or polyvinyl alcohol or copolymers thereof, and preferably one or more polymers not identical to said aliphatic and / or aliphatic-aromatic polyester, or said polyvinyl alcohol or copolymers thereof, of synthetic or natural origin, which may or may not be biodegradable, and preferably one or more other components.
[0027] As far as the polymers, biodegradable or not, of synthetic or natural origin, which are not the same as said aliphatic and / or aliphatic-aromatic polyesters or said polyvinyl alcohols or their copolymers are concerned, these are advantageously selected from the group consisting of polyhydroxyalkanoates, vinyl polymers, diacid-diol polyesters other than polyester i., polyamides, polyurethanes, polyethers, polyureas, polycarbonates and mixtures thereof. In the case of non-biodegradable polymers, they are obviously present in amounts such that they do not have a significant effect on the biodegradability of the final product.
[0028] A preferred embodiment of said composition in layer A comprises, in addition to said aliphatic and / or aliphatic-aromatic polyesters or said polyvinyl alcohol or copolymers thereof, between 1 and 40% by weight, and more preferably between 5 and 30% by weight, of at least one polyhydroxyalkanoate, more preferably a polyhydroxyalkanoate selected from the group consisting of polyesters of lactic acid, poly-ε-caprolactone, polyhydroxybutyric acid, polyhydroxybutyric acid-valeric acid, polyhydroxybutyric acid-propanoic acid, polyhydroxybutyric acid-hexanoic acid, polyhydroxybutyric acid-decanoic acid, polyhydroxybutyric acid-dodecanoic acid, polyhydroxybutyric acid-hexadecanoic acid, polyhydroxybutyric acid-octadecanoic acid, poly-3-hydroxybutyric acid-4-hydroxybutyric acid, relative to the total amount of layer A. Preferably, said polyhydroxyalkanoate comprises at least 80% by weight of one or more polyesters of lactic acid. Preferred embodiments of the lactic acid polyester are selected from the group consisting of poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid stereocomplexes, copolymers containing more than 50 mol % of said lactic acid polyesters or mixtures thereof. At least 95% by weight of the copolymer has a molecular weight Mw greater than 50,000, between 50 and 500 Pa.s, preferably 100-300 Pa.s (T=190° C., shear rate=1000 s -1Particularly preferred are lactic acid polyesters containing repeating units derived from L-lactic acid or D-lactic acid or combinations thereof having a shear viscosity of 0.01 to 0.15 (measured according to the ASTM D3835 standard at D=1 mm, L / D=10). In a particularly preferred embodiment of the invention, the lactic acid polyester comprises at least 95% by weight of units derived from L-lactic acid, ≦5% of repeating units derived from D-lactic acid, and has a melting point in the range of 135-180° C., a glass transition temperature (Tg) in the range of 55-65° C., and a MFR in the range of 1-50 g / 10 min (measured according to the ISO 1133-1 standard at 190° C. and 2.16 kg). Commercially available examples of lactic acid polyesters with these properties are e.g. Ingeo TM Biopolymer 4043D, 3251D and 6202D type products.
[0029] Among the vinyl polymers, preferred are polyethylene, polypropylene, copolymers thereof, polyvinyl alcohol, polyvinyl acetate, polyvinyl acetate and polyethylene vinyl alcohol, polystyrene, vinyl chloride polymers and polyacrylates. Among the vinyl chloride polymers intended to be included herein are, in addition to polyvinyl chloride, polyvinylidene chloride, chlorinated polyethylene, poly(vinyl chloride-vinyl acetate), poly(vinyl chloride-ethylene), poly(vinyl chloride-propylene), poly(vinyl chloride-styrene), poly(vinyl chloride-isobutylene) and copolymers representing greater than 50 mole percent polyvinyl chloride. The polymers may be random, block or alternating copolymers.
[0030] As far as the polyamides in the composition according to the invention are concerned, they are preferably selected from the group consisting of polyamides 6 and 6,6, polyamides 9 and 9,9, polyamides 10 and 10,10, polyamides 11 and 11,11, polyamides 12 and 12,12 and their combinations of type 6 / 9, 6 / 10, 6 / 11 and 6 / 12, mixtures thereof and both random and block copolymers.
[0031] Preferably, the polycarbonate of the composition according to the invention is selected from the group consisting of polyalkylene carbonates, more preferably polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, mixtures and random and block copolymers thereof.
[0032] Of the polyethers, preferred are those selected from the group consisting of polyethylene glycol, polypropylene glycol, polybutylene glycol, copolymers thereof and mixtures thereof having a molecular weight of from 70,000 to 500,000.
[0033] As far as the diacid diol polyesters, which are not the same as the aliphatic and / or aliphatic-aromatic polyesters in layer A, are concerned, these preferably comprise the following g) and h): g) For the total dicarboxylic acid components: g1) 20-100 mol % of units derived from at least one aromatic dicarboxylic acid; g2) 0-80 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; g3) 0-5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid Dicarboxylic acid component containing h) For the total diol content: h1) 95-100 mol % of units derived from at least one saturated aliphatic diol; h2) 0-5 mol % of units derived from at least one unsaturated aliphatic diol A diol component comprising: Preferably, the aromatic dicarboxylic acid g1, the saturated aliphatic dicarboxylic acid g2, the unsaturated aliphatic dicarboxylic acid g3, the saturated aliphatic diol h1 and the unsaturated aliphatic diol h2 are selected from those described above for the aliphatic-aromatic polyesters in layer A according to the invention.
[0034] At least one crosslinker and / or chain extender may also be present in the composition of layer A to improve the hydrolytic stability. The crosslinker and / or chain extender is selected from bi- and / or multi-functional compounds containing isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride or divinyl ether groups or mixtures thereof. Preferably, the crosslinker and / or chain extender comprises at least one bi- and / or multi-functional compound containing isocyanate groups. More preferably, the crosslinker and / or chain extender comprises at least 25% by weight of one or more bi- and / or multi-functional compounds containing isocyanate groups. It is particularly preferred to comprise a mixture comprising a bi- and / or multi-functional compound containing isocyanate groups and a bi- and / or multi-functional compound containing epoxy groups, more preferably at least 75% by weight of a bi- and / or multi-functional compound containing isocyanate groups.
[0035] Compounds having two and multiple functional groups, including isocyanate groups, are preferably p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4-diphenylmethane diisocyanate, 1,3-phenylene-4-chlorodiisocyanate, 1,5-naphthalene diisocyanate, 4,4-diphenylene diisocyanate, 3,3'-dimethyl-4,4-diphenylmethane diisocyanate, 3-methyl-4,4'-diphenylmethane diisocyanate, diphenyl ester diisocyanate, 2,4-cyclohexane diisocyanate, 2,3-cyclohexane diisocyanate, 1-methyl-2,4-cyclohexane diisocyanate, 1,5-naphthalene diisocyanate, 4,4-diphenylene diisocyanate, 3,3'-dimethyl-4,4-diphenylmethane diisocyanate, 3-methyl-4,4'-diphenylmethane diisocyanate, diphenyl ester diisocyanate, 2,4-cyclohexane diisocyanate, 1,5-naphthalene ... The isocyanate-containing compound is selected from the group consisting of cyclohexyl diisocyanate, 1-methyl 2,6-cyclohexyl diisocyanate, bis-(isocyanatocyclohexyl)methane, 2,4,6-toluene triisocyanate, 2,4,4-diphenyl ether triisocyanate, polymethylene-polyphenyl-polyisocyanate, methylene diphenyl diisocyanate, triphenylmethane triisocyanate, 3,3'ditolylene-4,4-diisocyanate, 4,4-methylenebis(2-methyl-phenylisocyanate), hexamethylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,2-cyclohexylene diisocyanate and mixtures thereof. A preferred embodiment of the compound containing isocyanate groups is 4,4-diphenylmethane diisocyanate.
[0036] As far as the compounds with two and / or multiple functional groups, including peroxide groups, are concerned, these are preferably selected from benzoyl peroxide, lauroyl peroxide, isononanoyl peroxide, di-(t-butylperoxyisopropyl)benzene, t-butyl peroxide, dicumyl peroxide, α,α-di(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(-butylperoxy)hexane, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hex-3-yne, di(4-t-butylcyclohexyl)peroxydicarbonate, dicetyl peroxydicarbonate, dimyristyl peroxydicarbonate, 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxane, di(2-ethylhexyl)peroxydicarbonate and mixtures thereof.
[0037] Compounds with two and / or multiple functional groups containing carbodiimide groups which are preferably used in the compositions according to the invention are poly(cyclooctylenecarbodiimide), poly(1,4-dimethylenecyclohexylenecarbodiimide), poly(cyclohexylenecarbodiimide), poly(ethylenecarbodiimide), poly(butylenecarbodiimide), poly(isobutylenecarbodiimide), poly(nonylenecarbodiimide), poly(dodecylenecarbodiimide), poly(neopentylenecarbodiimide), poly(1,4-dimethylenephenylenecarbodiimide), poly(2,2',6,6'-tetraisopropyldiphenylenecarbodiimide) (Stabaxol® D), poly(2,4,6-triisopropyl-1,3-phenylenecarbodiimide). (Stabaxol® P-100), poly(2,6 diisopropyl-1,3-phenylene carbodiimide) (Stabaxol® P), poly(tolylcarbodiimide), poly(4,4'-diphenylmethanecarbodiimide), poly(3,3'-dimethyl-4,4'-biphenylenecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(3,3'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(isophoronecarbodiimide), poly(cumenecarbodiimide), p-phenylenebis(ethylcarbodiimide), 1,6-hexamethylenebis(ethylcarbodiimide), 1,8-octamethylenebis(ethylcarbodiimide), 1,10-decamethylenebis(ethylcarbodiimide), 1,12dodecamethylenebis(ethylcarbodiimide) and mixtures thereof.
[0038] Examples of compounds with two and multiple functional groups, including epoxy groups, which can be advantageously used in the compositions according to the invention are all polyepoxides from epoxidized oils and / or styrene-glycidyl ether-methyl methacrylate or glycidyl ether-methyl methacrylate, which are included within the molecular weight range between 1000 and 10000 and have an epoxide number per molecule ranging from 1 to 30, and preferably between 5 and 25, the selected epoxides in the group being: diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, 1,2-epoxybutane, polyglycerol polyglycidyl ether, isoprene diepoxide, and cycloaliphatic diepoxides, 1,4-cyclohexanedimethanol diglycidyl ether, glycidyl 2-methylphenyl ether, glycerol propoxylatotriglycidyl ether, ether), 1,4-butanediol diglycidyl ether, sorbitol polyglycidyl ether, glycerol diglycidyl ether, the tetraglycidyl ether and diglycidyl ether of meta-xylylenediamide or bisphenol A and mixtures thereof.
[0039] With bi- and polyfunctional compounds, including isocyanates, peroxides, carbodiimides, isocyanurates, oxazolines, epoxies, anhydrides, and divinyl ether groups, such as those mentioned above, catalysts may also be used to enhance the reactivity of the reactive groups. In the case of polyepoxides, salts of fatty acids, more preferably calcium and zinc stearates, may be preferably used.
[0040] Particularly preferred embodiments of crosslinkers and / or chain extenders for the composition in layer A of the present invention comprise compounds containing isocyanate groups, preferably 4,4-diphenylmethane-diisocyanate, and / or carbodiimide groups and / or containing epoxy groups, preferably compounds of the styrene-glycidyl ether-methyl methacrylate type.
[0041] Fillers may also be present in the composition of Layer A in an amount of up to 10% by weight based on the total amount of Layer A.
[0042] The composition of Layer A of the multilayer film according to the present invention does not contain starch.
[0043] In addition to the above components, the composition in Layer A also preferably contains at least one other compound selected from the group consisting of plasticizers, UV stabilizers, lubricants, nucleating agents, surfactants, antistatic agents, pigments, flame retardants, compatibilizers, lignin, organic acids, antioxidants, antifungal agents, waxes, processing aids, and a polymer component preferably selected from the group consisting of vinyl polymers, diacid diol polyesters that are not the aliphatic-aromatic polyesters described above, polyamides, polyurethanes, polyethers, polyuric acids, or polycarbonates.
[0044] As far as the plasticizers are concerned, preferably in the composition of layer A according to the invention there are used water, polyols having from 2 to 22 carbon atoms, phthalates such as diisononyl phthalate, trimellitates such as C4-C phthalates selected from the group comprising preferably n-octanol and n-decanol. 20 One or more plasticizers are present, selected from the group including esters of monoalcohols and trimellitic acid, and aliphatic esters having the following structure: R1-O- C(O)-R4-C(O)-[-O-R2-OC(O)-R5-C(O)-] m -O-R3 Where: R1 is H, C1-C 24 Linear and branched saturated and unsaturated alkyl residues of the type C1-C 24 selected from one or more groups containing a polyol residue esterified with a monocarboxylic acid; R2 comprises -CH2-C(CH3)2-CH2- and C2-C8 alkylene groups and contains at least 50 mole % of said -CH2-C(CH3)2-CH2- groups; R3 is H, C1-C 24 Linear and branched saturated and unsaturated alkyl residues of the type C1-C 24selected from one or more groups containing a polyol residue esterified with a monocarboxylic acid; R4 and R5 may be the same or different and may be one or more of C2-C 22 , preferably C2-C 11 , more preferably C4-C9 alkylenes, and at least 50 mole % C7 alkylenes.
[0045] m is a number between 1 and 20, preferably 2-10, more preferably 3-7. Preferably, in said ester, at least one of the R1 and / or R3 groups is at least one C1-C stearic acid selected from the group consisting of stearic acid, palmitic acid, 9-ketostearic acid, 10-ketostearic acid and mixtures thereof, preferably comprising an amount of ≧10 mol %, more preferably ≧20 mol %, even more preferably ≧25 mol % based on the amount of total R1 and / or R3 groups. 24 They comprise a polyol residue esterified with a monocarboxylic acid. Examples of this type of aliphatic ester are described in Italian Patent Application MI2014A000030 and PCT Applications PCT / EP2015 / 050336, PCT / EP2015 / 050338.
[0046] The plasticizer selected when present in Layer A is preferably present at up to 10% by weight, based on the total weight of the composition of Layer A itself.
[0047] The lubricant is preferably selected from esters and metal salts of fatty acids, such as zinc stearate, calcium stearate, aluminum stearate and acetyl stearate.Preferably, the layer A composition according to the present invention comprises up to 1 wt. % of a lubricant, more preferably up to 0.5 wt. %, based on the total weight of the layer A composition.
[0048] Examples of nucleating agents include sodium salt of saccharin, calcium silicate, sodium benzoate, calcium titanate, boron nitride, isotactic polypropylene, or low molecular weight PLA. These additives are preferably added in an amount of up to 10% by weight, and more preferably between 2 and 6% by weight, based on the total weight of the composition. Pigments may also be added if necessary, such as titanium dioxide, clay, copper phthalocyanine, titanium dioxide, silicates, iron oxides and hydroxides, carbon black, and magnesium oxide. These additives are preferably added in an amount of up to 10% by weight.
[0049] A preferred embodiment of layer A of the multilayer film according to the invention comprises, for the sum of components i.-v.: i) 30-70% by weight of at least one aliphatic-aromatic polyester; ii) 20-60% by weight of at least one aliphatic polyester; iii) 1-20% by weight of at least one polyhydroxyalkanoate; iv) 0-5% by weight, preferably 0-0.5%, of at least one crosslinker and / or chain extender comprising at least one compound with bi- and / or multi-functional groups including isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride or divinyl ether groups and mixtures thereof; v) 0-10% by weight, preferably 0-5% of at least one filler Includes.
[0050] A preferred embodiment of layer A of the multilayer film according to the invention comprises, for the sum of components i.-v.: i) 60-100% by weight of at least one aliphatic-aromatic polyester; ii) 0-20% by weight of at least one aliphatic polyester; iii) 0-40% by weight of at least one polyhydroxyalkanoate; iv) 0-5% by weight, preferably 0-0.5%, of at least one crosslinker and / or chain extender comprising at least one compound with bi- and / or multi-functional groups including isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride or divinyl ether groups and mixtures thereof; v) 0-10% by weight, preferably 0-5% of at least one filler Includes.
[0051] A preferred embodiment of layer A of the multilayer film according to the invention comprises, for the sum of components i.-v.: i) 0-20% by weight of at least one aliphatic-aromatic polyester; ii) 60-100% by weight of at least one aliphatic polyester; iii) 0-40% by weight of at least one polyhydroxyalkanoate; iv) 0-5% by weight, preferably 0-0.5%, of at least one crosslinker and / or chain extender comprising at least one compound with bi- and / or multi-functional groups including isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride or divinyl ether groups and mixtures thereof; v) 0-10% by weight, preferably 0-5% of at least one filler Includes.
[0052] Layer B As far as layer B is concerned, this is: i) 30-95% by weight, preferably 50-85% by weight, relative to the sum of components i.-v., of at least one polyester comprising a) and b) of: a) for the total dicarboxylic acid component: a1) 35-70 mol %, preferably 40-60 mol %, more preferably 45-60 mol % of units derived from at least one aromatic dicarboxylic acid; a2) 70-35 mol %, preferably 60-40 mol %, more preferably 55-40 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; a3) 0-5 mol % of units derived from unsaturated aliphatic dicarboxylic acids; A dicarboxylic acid component comprising: b) For the total diol content: b1) 95-100 mol % of units derived from at least one saturated aliphatic diol; b2) 0-5 mol % of units derived from at least one unsaturated aliphatic diol; A diol component comprising: ii) 0.1-50% by weight, preferably 5-40% by weight, of at least one polymer of natural origin, relative to the sum of components i.-v., iii) 1-40% by weight, preferably 2-30% by weight, relative to the sum of components i.-v., of at least one polyhydroxyalkanoate; iv) 0-15% by weight, based on the sum of components i.-v., of at least one inorganic filler; v) 0-5% by weight, preferably 0-0.5% by weight, based on the sum of components i.-v., of at least one crosslinker and / or chain extender, comprising at least one compound with bi- and / or multi-functional groups, including isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxide, anhydride and divinyl ether groups and mixtures thereof. Includes.
[0053] The aromatic dicarboxylic acids in component a1 of polyester i are preferably chosen from aromatic dicarboxylic acids of the phthalic acid type, preferably terephthalic acid or isophthalic acid, more preferably terephthalic acid and heterocyclic dicarboxylic aromatic compounds, preferably 2,5-furandicarboxylic acid, 2,4-furandicarboxylic acid, 2,3-furandicarboxylic acid, 3,4-furandicarboxylic acid, more preferably 2,5-furandicarboxylic acid, esters, salts and mixtures thereof. Preferred embodiments of said aromatic dicarboxylic acids are: - 1 to 99 mol %, preferably 5 to 95 mol %, and more preferably 10 to 80 mol % of terephthalic acid, its esters or salts; - 99 to 1 mol %, preferably 95 to 5 mol %, and more preferably 90 to 20 mol % of 2,5-furandicarboxylic acid, an ester or a salt thereof Includes.
[0054] The saturated aliphatic dicarboxylic acid in component a2 of polyester i is preferably a saturated C2-C 24 , preferably C4-C 13 , more preferably C4-C 11 Dicarboxylic acids, those C1-C 24 , preferably C1-C4, alkyl esters, salts thereof and mixtures thereof. Preferred saturated aliphatic dicarboxylic acids are succinic acid, 2-ethylsuccinic acid, glutaric acid, 2-methylglutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecane diacid, dodecane diacid, brassylic acid, hexadecanedioic acid, octadecanedioic acid and their C1-C4 alkyl esters, salts thereof and mixtures thereof. 24 A preferred embodiment of the saturated aliphatic dicarboxylic acid of the present invention is selected from the group consisting of succinic acid, adipic acid, azelaic acid, sebacic acid, brassylic acid, and their C1-C alkyl esters, at least 50 mol %, preferably 60 mol % or more, more preferably more than 65 mol %. 24 Particularly preferred embodiments of the mixtures include mixtures comprising adipic acid and azelaic acid, and the azelaic acid is present in an amount of between 5 and 40 mol %, more preferably between 10 and 35 mol %, based on the sum of adipic acid and azelaic acid. Contains phosphate.
[0055] The unsaturated aliphatic dicarboxylic acids in component a3 of polyester i are preferably itaconic acid, fumaric acid, 4-methylenepimelic acid, 3,4-bis(methylene)nonanedioic acid, 5-methylene-nonanedioic acid, their C1-C 24 A preferred embodiment of the unsaturated aliphatic dicarboxylic acid of the present invention is selected from at least 50 mol %, preferably more than 60 mol %, more preferably more than 65 mol % itaconic acid and its C1-C4 alkyl esters, their salts and mixtures thereof.24 , preferably C1-C4, and mixtures including esters. More preferably, the unsaturated aliphatic dicarboxylic acid comprises itaconic acid.
[0056] As far as the saturated aliphatic diols in component b1 of the polyesters i are concerned, these are preferably selected from 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, 2-methyl-1,3-propanediol, dianhydrosorbitol, dianhydromannitol, dianhydroiditol, cyclohexanediol, cyclohexanemethanediol, dialkene glycols and polyalkylene glycols having a molecular weight of 100-4000, such as polyethylene glycol, polypropylene glycol, and mixtures thereof. A preferred diol component comprises at least 50 mol % of one or more diols selected from 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, and more preferably the diol component comprises or consists of 1,4-butanediol.
[0057] As far as the unsaturated aliphatic diols in component b2 of the polyester i are concerned, these are preferably cis 2-butene-1,4-diol, trans 2-butene-1,4-diol, 2-butyne-1,4-diol, cis 2-pentene-1,5-diol, trans 2-pentene-1,5-diol, 2-pentyne-1,5-diol, cis 2-hexene-1,6-diol, trans 2-hexene-1,6-diol, 2-hexyne-1,6-diol, cis 3-hexene-1,6-diol, trans 3-hexene-1,6-diol, and 3-hexyne-1,6-diol.
[0058] The Mn molecular weight of the polyester i in layer B is preferably ≧20 000, more preferably ≧40 000. As far as the molecular weight polydispersity index, Mw / Mn, is concerned, this is instead preferably between 1.5 and 10, more preferably between 1.6 and 5, and even more preferably between 1.8 and 2.7. The Mn and Mw molecular weights can be measured using Gel Permeation Chromatography (GPC). The determination can be performed using a chromatographic system maintained at 40° C., a set of two columns in series (particle sizes 5 μm and 3 μm with mixed porosity), a refractive index detector, chloroform as eluent (flow rate 0.5 ml / min), and polystyrene as reference standard.
[0059] The terminal acid group content of the polyester i in layer B is preferably less than 100 meq / kg, preferably less than 60 meq / kg, and more preferably less than 40 meq / kg. The acidic terminal group content can be measured using the method described for the Layer A aliphatic-aromatic polyester.
[0060] The polyester i in the preferred layer B has an inherent viscosity of 0.3 dl / g or more (measured using an Ubbelohde viscometer for a solution of 0.2 g / dl concentration in CHCl3 at 25°C), preferably between 0.3 and 2 dl / g, more preferably between 0.4 and 1.1 dl / g.
[0061] Preferably, said polyester i in layer B is biodegradable. By biodegradable polymers the invention means polymers which are biodegradable according to standard EN13432.
[0062] Said polyester i in layer B may be synthesised by any method known in the art, in particular advantageously by means of a polycondensation reaction.
[0063] Advantageously, the synthesis process may be carried out in the presence of a suitable catalyst, such as organometallic, for example stannic acid derivatives of tin, titanium compounds, for example orthobutyl titanate, aluminum compounds, for example triisopropylaluminum, antimony and zinc and zirconium compounds and mixtures thereof.
[0064] The composition of layer B comprises 0.1-50% by weight, preferably 5-40% by weight, of at least one naturally occurring polymer, relative to the sum of components i.-v. In the composition of layer B, the naturally occurring polymer (component ii) is advantageously chosen from starch, chitin, chitosan, alginates, proteins such as gluten, zein, casein, collagen, gelatin, natural gums, rosin acids and their derivatives. Preferably, the naturally occurring polymer in the composition of layer B is starch.
[0065] The term starch refers to all types of starch, i.e. biofillers including flour, native starch, hydrolyzed starch, degraded starch, gelatinized starch, plasticized starch, thermoplastic starch, complex starch or mixtures thereof. Particularly suitable for the present invention are starches derived from, for example, potato, corn, tapioca and pea. Starches which have the ability to be easily degraded or which have a high initial molecular weight, such as potato or corn starch, have proven particularly advantageous. The starch may be present as such or in a chemically modified form, such as, for example, starch esters having a degree of substitution between 0.2 and 2.5, starch hydroxypropyl or starches modified with fatty chains.
[0066] In the case of degraded starch, reference is made here to the teachings contained in patents EP-0118240 and EP-0327505, and it is meant starch treated in such a way as to be substantially free from so-called "Maltese crosses" in optical microscopy under polarized light and from so-called "ghosts" in optical microscopy under phase contrast. Advantageously, the starch is degraded in an extrusion process at a temperature between 110 and 250°C, preferably between 130-180°C, preferably at a pressure of 0.1 to 7 MPa, preferably 0.3-6 MPa, preferably providing a specific energy during said extrusion greater than 0.1 kWh / kg. The degradation of the starch preferably takes place in the presence of 1-40% by weight, relative to the weight of the starch, of one or more plasticizers selected from water and polyols having from 2 to 22 carbon atoms. As far as water is concerned, it may be that which is naturally present in the starch. Among the polyols, preference is given to polyols having from 1 to 20 hydroxyl groups containing from 2 to 6 carbon atoms, their ethers, thioethers and organic and inorganic esters. Examples of polyols are glycerin, diglycerol, polyglycerol, pentaerythritol, polyglycerol ethoxylates, ethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, sorbitol monoacetate, sorbitol diacetate, sorbitol monoethoxylate, sorbitol diethoxylate and mixtures thereof. In a preferred embodiment, the starch is degraded in the presence of glycerol or a mixture of plasticizers containing glycerol, more preferably between 2 and 0% by weight of glycerol. The degraded and crosslinked starch according to the invention is preferably starch. The composition contains between 1 and 40% by weight of a plasticizer based on the weight of the composition.
[0067] When present, the starch in the composition of layer B is preferably in the form of particles having a circular or elliptical cross section, or in any case a cross section resembling an ellipse, which have an arithmetic mean diameter, measured along the major axis of the particle, of less than 1 micron, more preferably an average diameter of less than 0.5 μm.
[0068] The composition of layer B comprises 1-40% by weight, preferably 2-30% by weight, relative to the sum of components i.-v., of at least one polyhydroxyalkanoate (component iii), preferably selected from the group consisting of polyesters of lactic acid, poly-ε-caprolactone, polyhydroxybutyrate, polyhydroxybutyrate-valerate, polyhydroxybutyrate-propanoate, polyhydroxybutyrate-hexanoate, polyhydroxybutyrate-decanoate, polyhydroxybutyrate-dodecanoate, polyhydroxybutyrate-hexadecanoate, polyhydroxybutyrate-octadecanoate, poly-3-hydroxybutyrate-4-hydroxybutyrate. Preferably, said polyhydroxyalkanoate comprises at least 80% by weight of one or more polyesters of lactic acid. Preferred embodiments of the lactic acid polyester are selected from the group consisting of poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid stereocomplexes, copolymers containing more than 50 mol % of said lactic acid polyesters, or mixtures thereof. Particularly preferred lactic acid polyesters have at least 95% by weight of a molecular weight Mw greater than 50,000, a shear viscosity between 50 and 500 Pa.s, preferably 100-300 Pa.s (T=190° C., shear rate=1000 s -1 , D=1 mm, L / D=10, measured according to the ASTM D3835 standard.
[0069] In a particularly preferred embodiment of the invention, the lactic acid polyester has at least 95% by weight of units derived from L-lactic acid, ≦5% of repeat units derived from D-lactic acid, and comprises a melting point in the range of 135-180° C., a glass transition temperature (Tg) in the range of 55-65° C., and a MFR in the range of 1-50 g / 10 min (measured according to the ISO 1133-1 standard at 190° C. and 2.16 kg). Commercially available examples of lactic acid polyesters having these properties are e.g. Ingeo TM Biopolymer 4043D, 3251D and 6202D type products.
[0070] In the composition of layer B, 0-15% by weight, relative to the sum of components i.-v., of at least one inorganic filler (component iv), preferably selected from kaolin, baryte flour, clay, talc, carbonates of calcium and magnesium, iron and lead, ammonium hydroxide, diatomaceous earth, aluminum sulfate, barium sulfate, silica, mica, titanium dioxide, wollastonite.
[0071] In a preferred embodiment of the invention, the mineral filler in the composition of layer B comprises talc, calcium carbonate or a mixture thereof, present in the form of particles having an arithmetic mean diameter, measured relative to the longest axis of the particle, of less than 10 microns. Fillers of the above types, which are not characterized by said mean arithmetic diameter, have in fact demonstrated a significant decrease in disintegration properties during industrial composting of objects containing them. In the composition of layer B, at least one crosslinker and / or chain extender (component v.) is also present in an amount of 0 to 5% by weight, preferably 0-0.5% by weight, based on the sum of components i.-v., in order to increase the hydrolytic stability.
[0072] The crosslinking agent and / or chain extender is selected from bifunctional and / or multifunctional compounds containing isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride or divinyl ether groups or mixtures thereof. A preferred crosslinking agent and / or chain extender comprises at least one bifunctional and / or multifunctional compound containing isocyanate groups. More preferred crosslinking agents and / or chain extenders comprise at least 25% by weight of one or more bifunctional and / or multifunctional compounds containing isocyanate groups. Particularly preferred are mixtures of bifunctional and / or multifunctional compounds containing isocyanate groups and bifunctional and / or multifunctional compounds containing epoxy groups, even more preferred at least 75% by weight of bifunctional and / or multifunctional compounds containing isocyanate groups.
[0073] The bifunctional and / or multifunctional compounds containing isocyanate groups are preferably p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4-diphenylmethane diisocyanate, 1,3-phenylene-4-chlorodiisocyanate, 1,5-naphthalene diisocyanate, 4,4-diphenylene diisocyanate, 3,3'-dimethyl-4,4-diphenylmethane diisocyanate, 3-methyl-4,4'-diphenylmethane diisocyanate, diphenyl ester diisocyanate, 2,4-cyclohexane diisocyanate, 2,3-cyclohexane diisocyanate, 1-methyl 2,4- The isocyanate is selected from cyclohexyl diisocyanate, 1-methyl 2,6-cyclohexyl diisocyanate, bis-(isocyanatocyclohexyl)methane, 2,4,6-toluene triisocyanate, 2,4,4-diphenyl ether triisocyanate, polymethylene-polyphenyl-polyisocyanate, methylene diphenyl diisocyanate, triphenylmethane triisocyanate, 3,3'ditolylene-4,4-diisocyanate, 4,4'-methylenebis(2-methylphenylisocyanate), hexamethylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,2-cyclohexylene diisocyanate and mixtures thereof. A preferred embodiment of the compound containing isocyanate groups is 4,4-diphenylmethane-diisocyanate.
[0074] As far as the compounds with two and / or multiple functional groups, including peroxide groups, are concerned, these are preferably selected from benzoyl peroxide, lauroyl peroxide, isononanoyl peroxide, di-(t-butylperoxyisopropyl)benzene, t-butyl peroxide, dicumyl peroxide, α,α-di(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hex-3-yne, di(4-t-butylcyclohexyl)peroxydicarbonate, dicetyl peroxydicarbonate, dimyristyl peroxydicarbonate, 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxane, di(2-ethylhexyl)peroxydicarbonate and mixtures thereof.
[0075] Compounds with two and / or multiple functional groups containing carbodiimide groups which are preferably used in the compositions according to the invention are poly(cyclooctylenecarbodiimide), poly(1,4-dimethylenecyclohexylenecarbodiimide), poly(cyclohexylenecarbodiimide), poly(ethylenecarbodiimide), poly(butylenecarbodiimide), poly(isobutylenecarbodiimide), poly(nonylenecarbodiimide), poly(dodecylenecarbodiimide), poly(neopentylenecarbodiimide), poly(1,4-dimethylenephenylenecarbodiimide), poly(2,2',6,6'-tetraisopropyldiphenylenecarbodiimide) (Stabaxol® D), poly(2,4,6-triisopropyl-1,3-phenylenecarbodiimide). (Stabaxol® P-100), poly(2,6 diisopropyl-1,3-phenylene carbodiimide) (Stabaxol® P), poly(tolylcarbodiimide), poly(4,4'-diphenylmethanecarbodiimide), poly(3,3'-dimethyl-4,4'-biphenylenecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(3,3'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(isophoronecarbodiimide), poly(cumenecarbodiimide), p-phenylenebis(ethylcarbodiimide), 1,6-hexamethylenebis(ethylcarbodiimide), 1,8-octamethylenebis(ethylcarbodiimide), 1,10-decamethylenebis(ethylcarbodiimide), 1,12dodecamethylenebis(ethylcarbodiimide) and mixtures thereof.
[0076] Examples of compounds with bifunctional and polyfunctional groups, including epoxy groups, which may be advantageously used in the compositions according to the invention are all polyepoxides derived from epoxidized oils and / or styrene-glycidyl ether-methyl methacrylate or glycidyl ether-methyl methacrylate, included within the molecular weight range between 1000 and 10000, and having an epoxide number per molecule ranging from 1 to 30, and preferably between 5 and 25, the selected epoxides in the group being diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, 1,2-epoxybutane, polyglycerol polyglycidyl ether, isoprene diepoxide, and cycloaliphatic diepoxides, 1,4-cyclohexanedimethanol diglycidyl ether, glycidyl 2-methylphenyl ether, glycerol propoxylatotriglycidyl ether, ether), 1,4-butanediol diglycidyl ether, sorbitol polyglycidyl ether, glycerol diglycidyl ether, meta-xylylenediamide and diglycidyl ether or the tetraglycidyl ether of bisphenol A and mixtures thereof.
[0077] For example, with these bi- and polyfunctional compounds including isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride and divinyl ether groups mentioned above, catalysts may also be used to enhance the reactivity of the reactive groups. In the case of polyepoxides, salts of fatty acids may be preferably used, more preferably calcium stearate and zinc stearate.
[0078] Particularly preferred embodiments of crosslinkers and / or chain extenders for the composition in layer B of the present invention comprise compounds containing isocyanate groups, preferably 4,4-diphenylmethane-diisocyanate, and / or compounds containing carbodiimide groups, and / or compounds containing epoxy groups, preferably of the styrene-glycidyl ether-methyl methacrylate type. In addition to the above-mentioned components i.-v. in layer B, one or more other compounds are advantageously also present. In this case, layer B comprises a composition comprising components i.-v. and preferably one or more polymers, which may or may not be biodegradable, and which are not the same as components i., ii. and iii., of synthetic or natural origin, optionally together with one or more other components.
[0079] Same as i., ii. and iii., synthetic or natural components which may or may not be biodegradable. As far as the non-polyester polymers are concerned, they are advantageously chosen from vinyl polymers, non-polyester diacid diol polyesters, polyamides, polyurethanes, polyethers, polyureas, polycarbonates and mixtures thereof.
[0080] Of the vinyl polymers, preferred are polyethylene, polypropylene, copolymers thereof, polyvinyl alcohol, polyvinyl acetate, polyvinyl acetate and polyethylene vinyl alcohol, polystyrene, chlorinated vinyl polymers and polyacrylates. Among the chlorinated vinyl polymers intended to be included herein are, in addition to polyvinyl chloride, polyvinylidene chloride, chlorinated polyethylene, poly(vinyl chloride-vinyl acetate), poly(vinyl chloride-ethylene), poly(vinyl chloride-propylene), poly(vinyl chloride-styrene), poly(vinyl chloride-isobutylene) and copolymers in which polyvinyl chloride represents more than 50 mole percent. The polymers may be random, block or alternating copolymers.
[0081] As far as the polyamides in the composition according to the invention are concerned, they are preferably selected from the group comprising polyamides 6 and 6,6, polyamides 9 and 9,9, polyamides 10 and 10,10, polyamides 11 and 11,11, polyamides 12 and 12,12 and combinations thereof of the 6 / 9, 6 / 10, 6 / 11 and 6 / 12 type, mixtures thereof and random and block copolymers of both.
[0082] Preferred polycarbonates of the composition according to the invention are selected from the group comprising polyalkylene carbonates, more preferably polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, mixtures and random and block copolymers thereof.
[0083] Of the polyethers, preferred are those selected from the group consisting of polyethylene glycol, polypropylene glycol, polybutylene glycol, copolymers thereof and mixtures thereof having molecular weights of from 70,000 to 500,000.
[0084] As far as the diacid diol polyesters, which are not the same as the polyesters i. in layer B, are concerned, these are preferably: i) for the total dicarboxylic acid components: i1) 20-100 mol % of units derived from at least one aromatic dicarboxylic acid; i2) 0-80 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; i3) 0-5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid; A dicarboxylic acid component comprising: j) For the total diol content: j1) 95-100 mol % of units derived from at least one saturated aliphatic diol; j2) 0-5 mol % of units derived from at least one unsaturated aliphatic diol A diol component comprising: Includes.
[0085] Preferred aromatic dicarboxylic acids i1, saturated aliphatic dicarboxylic acids i2, unsaturated aliphatic dicarboxylic acids i3, saturated aliphatic diols j1 and unsaturated aliphatic diols j2 for said polyesters are selected from those mentioned above for the polyesters i in layer B according to the invention.
[0086] In addition to the above components, the composition in Layer B preferably also contains at least one other compound selected from the group consisting of plasticizers, UV stabilizers, lubricants, nucleating agents, surfactants, antistatic agents, pigments, flame retardants, compatibilizers, lignin, organic acids, antioxidants, antifungal agents, waxes, processing aids, and a polymer component preferably selected from the group consisting of vinyl polymers, diacid diol polyesters that are not the aliphatic-aromatic polyesters described above, polyamides, polyurethanes, polyethers, polyureas, or polycarbonates.
[0087] As far as the plasticizers are concerned, in addition to the plasticizers preferably used for the preparation of degraded starch as described above, in the composition of layer B according to the invention, preferably phthalates, such as diisononyl phthalate, trimellitates, such as C4-C phthalates, preferably selected from the group comprising n-octanol and n-decanol, are used. 20 One or more plasticizers are present, selected from the group consisting of esters of monoalcohols and trimellitic acid, and aliphatic esters having the following structure: R1-O- C(O)-R4-C(O)-[-O-R2-OC(O)-R5-C(O)-] m -O-R3 Where: R1 is H, C1-C 24 Linear and branched saturated and unsaturated alkyl residues of the type C1-C 24 selected from one or more groups containing a polyol residue esterified with a monocarboxylic acid; R2 comprises -CH2-C(CH3)2-CH2- and C2-C8 alkylene groups and contains at least 50 mole % of said -CH2-C(CH3)2-CH2- groups; R3 is H, C1-C 24 Linear and branched saturated and unsaturated alkyl residues of the type C1-C 24 selected from one or more groups containing a polyol residue esterified with a monocarboxylic acid; R4 and R5 may be the same or different and may be one or more of C2-C 22 , preferably C2-C 11, more preferably C4-C9 alkylenes, and at least 50 mole % C7 alkylenes.
[0088] m is a number from 1 to 20, preferably 2-10, more preferably 3-7. Preferably, in said ester, at least one of the R1 and / or R3 groups is at least one C1-C stearic acid selected from the group consisting of stearic acid, palmitic acid, 9-ketostearic acid, 10-ketostearic acid and mixtures thereof, preferably comprising an amount of ≧10 mol %, more preferably ≧20 mol %, even more preferably ≧25 mol % based on the amount of the total R1 and / or R3 groups. 24 They comprise a polyol residue esterified with a monocarboxylic acid. Examples of this type of aliphatic ester are described in Italian Patent Application MI2014A000030 and PCT Applications PCT / EP2015 / 050336, PCT / EP2015 / 050338.
[0089] When present in Layer B, the selected plasticizer is preferably present at up to 10% by weight, based on the total weight of the composition of Layer B itself.
[0090] The lubricant is preferably selected from esters and metal salts of fatty acids, such as zinc stearate, calcium stearate, aluminum stearate, and acetyl stearate. Preferably, the Layer B composition according to the present invention comprises up to 1 wt. % of a lubricant, more preferably up to 0.5 wt. %, based on the total weight of the Layer B composition.
[0091] Examples of nucleating agents include the sodium salt of saccharin, calcium silicate, sodium benzoate, calcium titanate, boron nitride, isotactic polypropylene, or low molecular weight PLA. These additives are preferably added in an amount of up to 10% by weight, and more preferably between 2 and 6% by weight, based on the total weight of the composition.
[0092] Pigments may also be added if desired, such as titanium dioxide, clay, copper phthalocyanine, silicates, iron oxides and hydroxides, carbon black and magnesium oxide. These additives are preferably added at up to 10% by weight.
[0093] Preferably, the polyesters of layers A and / or B of the multilayer film according to the invention comprise at least 10 mol % of aromatic and / or aliphatic dicarboxylic acids and / or diols of renewable origin. According to the invention, products that can be considered of renewable origin are essentially those that are obtained from sources that are renewable and inexhaustible on the time scale of human life and whose use results in no adverse impact on the availability of natural resources by future generations. Examples of monomers of renewable origin are sebacic acid, succinic acid, 2,5-furandicarboxylic acid, azelaic acid, 1,4-butanediol.
[0094] The multilayer film according to the invention comprises at least one layer A and at least one layer B, preferably characterized by a correlation selected from A / B and A / B / A, said layers A and B being different, respectively. The multilayer film according to the invention advantageously comprises one or more layers A and one or more layers B as well as further layers, such as tie or barrier layers, or metal films. In the multilayer film according to the invention, the ratio between the total of layers A and the total of layers B is between 0.05 and 1.2. Preferably, in the multilayer film according to the invention, the ratio between the total of layers A and the total of layers B is between 0.1 and 0.6. The multilayer film according to the invention has a layer sequence of A / B and preferably A / B / A type, with the sum of the thicknesses of the A layers being less than the thickness of the B layers, preferably less than B / 2 and more preferably less than B / 3, in total. The multilayer film according to the invention advantageously has a total thickness of less than 50 microns, more preferably less than 15 microns, even more preferably less than 13 microns. The layer thickness may advantageously be measured using an electron microscope on a fracture surface in liquid nitrogen. However, there may also be further layers in an intermediate arrangement relative to layers A and B (arrangement A / C / B, where C is the further layer) or further layers in a non-intermediate arrangement (arrangement A / B / C or C / A / B, where C is the further layer).
[0095] The multilayer film according to the invention can be produced by any method known in the art, such as coextrusion, coating / spraying, or lamination. A preferred embodiment of the multilayer film according to the invention can be obtained through a coextrusion method, preferably accompanied by a bubble film forming process. The equipment and specific process conditions, for example for coextrusion and film forming, for the production of the multilayer film according to the invention depend on the composition and the number of layers intended to produce the multilayer film. As a result of the specific combination of components and layers, the multilayer film according to the invention has properties that provide an optimal balance between the properties of a high level of biodegradability, mechanical properties, especially a high modulus, and the properties of considerable light transmission. This provides a film that is particularly suitable for the production of a wide range of articles comprising said multilayer film, such as various types of packaging, especially bags for carrying goods and bags for food packaging, such as bags for fruits and vegetables.
[0096] As far as the optical properties are concerned, particularly preferred are transmittance values greater than 90%, more preferably greater than 91%, haze values less than 65%, more preferably less than 55% and transparency values greater than 20%, more preferably greater than 40% (measured according to the ASTM D1003 standard), which enable the multilayer films according to the invention to be particularly suitable for the abovementioned applications.
[0097] The multilayer film according to the invention is biodegradable under home composting conditions according to UNI 11355. Preferably, said multilayer film is biodegradable under home composting conditions according to UNI 1135 when characterized by a total thickness of less than 15 microns, preferably less than 13 microns.
[0098] The multilayer film according to the invention finds application in the manufacture of mulching films thanks to its high and constant degradability at low temperatures combined with strong mechanical properties, and therefore capable of effectively performing their functions of protecting the ground, for example preventing the growth of weeds and reducing water consumption, without the need to remove it after use. Preferably, the decomposition of the mulching film comprising the composition according to the invention occurs in the ground at a temperature of 28±2° C., and the degree of decomposition can be determined visually through regular observation. Preferably, the multi-layer film according to the invention will no longer be visible after 180 days.
[0099] The present invention will now be described based on a number of examples, which are not intended to be limiting of the invention. EXAMPLES
[0100] Example 1 - Two-layer film with A / B arrangement Preparation of Composition A (Layer A): 29.7 kg / h of poly(butylene adipic acid-co-butylene terephthalic acid) with a terephthalic acid content of 47.5 mol % based on the total dicarboxylic acid content, a MFR of 11 g / 10 min (190° C., 2.16 kg) and an acidity of 50 meq / kg, 9.1 k / h of Ingeo 3251D polylactic acid ("PLA") with a MFR of 58 g / 10 min (190° C., 2.16 kg), 1.0 kg / h of a masterbatch containing 10 wt % Joncryl ADR4368CS (styrene-glycidyl ether-methyl methacrylic acid copolymer) and 90 wt % Ingeo 40403D polylactic acid ("PLA"), 10 wt % Crodamide SR Beads and 90 wt % poly(butylene) manufactured by Croda. Adipic acid-co-butylene terephthalic acid) 0.2 kg / h masterbatch -Batch under the following conditions: Screw diameter (D) = 58 mm; L / D=36; Screw rotation speed = 140 rpm; Thermal profile = 60-150-180-210x-4-150x2℃; Throughput: 40kg / h; Vacuum degassing in zones 10 to 8 The mixture was fed into an OMCEBV60 / 36 twin screw extruder operated at 400rpm.
[0101] The so obtained granules had an MFR of 7 g / 10 min (190° C., 2.16 kg, based on ISO standard 1133-1 “Plastics - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard methods”). Preparation of Composition B (Layer B): 28.3 kg / h of poly(butylene adipic acid-co-butylene azelaic acid-co-butylene terephthalic acid) having an azelaic acid content of 30 mol % based on the sum of adipic acid and azelaic acid and a terephthalic acid content of 48.3 mol % based on the total dicarboxylic acid content, an MFR of 5 g / 10 min (190° C., 2.16 kg) and an acidity of 47 meq / kg, 1.4 kg / hm Ingeo 4043D polylactic acid (''PLA'') with an MFR of 2.7 g / 10 min (190° C., 2.16 kg), 16 kg / h of thermoplastic corn starch, 0.1 kg / h of Almatex PD-4440 manufactured by Anderson Development Company, 0.1 kg / h of Croamide ER microbeads manufactured by Croda and Nisshinbo Chemical Carbodilite HMV15CA manufactured by Carbodilite Inc. at 0.1 kg / h under the following conditions: Screw diameter (D) = 58 mm; L / D=36; Screw rotation speed = 160 rpm; Thermal profile = 60-150-180-210x-4-150x2℃; Throughput: 46.1kg / h; Vacuum degassing in zones 10 to 8 The mixture was fed into an OMC EBV60 / 36 twin screw extruder operated at 400°C.
[0102] The so obtained granules had an MFR of 2.4 g / 10 min (160° C., 5 kg, based on ISO standard 1133-1 “Plastics - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard methods”).
[0103] Composition A and composition B were then fed simultaneously to a coextruder to form a bilayer blown film with an A / B configuration. For this purpose, composition A was fed to an extruder with a screw diameter of 35 mm and L / D of 30, using a 100-170x4 temperature profile and operating at 13 rpm, with a throughput of 3.3 kg / h. At the same time, composition B was fed through two extruders, the first of which was characterized by a screw diameter of 35 mm with L / D of 30, with a 80-154x4 temperature profile and operating at 12 rpm, operated at 3.3 kg / h, and the second extruder was characterized by a screw diameter of 40 mm with L / D of 30, with a 80-145x4 temperature profile and operating at 74 rpm, and operated at a throughput of 28.3 kg / h. Once melted, the two compositions were fused in a dynamic extrusion blow head with a gap of 0.9 mm and L / D 9 set at 170°C to feed a multi-layer structure into a film forming process operating at a blow ratio of 4.5 and a stretch ratio of 20.2. The film so obtained (total 10 microns, 10% layer A, 90% layer B) was then characterized in terms of mechanical and optical properties (Table 1).
[0104] Example 2 - Two-layer film with A / B / A arrangement According to Example 1, composition A and composition B were fed simultaneously to a coextruder to form a three-layer blown film with an A / B / A configuration. For this purpose, composition A was fed with a throughput of 3.3 kg / h to a first extruder with a screw of 35 mm diameter and L / D of 30 with a 100-170x4 temperature profile and operating at 14 rpm, and with a throughput of 3.3 kg / h to a second extruder characterized by a screw of 35 mm diameter and L / D of 30 with a 100-170x4 temperature profile and operating at 13 rpm. Composition B was fed with a throughput of 28.3 kg / h to an extruder with a screw of 40 mm diameter and L / D of 30 with a 80-154x4 temperature profile and operating at 74 rpm. Once melted, the two compositions were fused in a dynamic extrusion blow head with a gap of 0.9 mm and L / D 9 set at 170°C to feed a multi-layer structure into a film forming process operating at a blow ratio of 4.5 and a stretch ratio of 20.2. The film so obtained (total 10 microns, 20% layer A, evenly distributed between the two layers, 80% layer B) was then characterized in terms of mechanical and optical properties (Table 1).
[0105] Example 3 (Comparative) Preparation of a Monolayer Film Containing Composition B Composition B was simultaneously fed to coextruders to form a monolayer blown film with a B / B / B configuration according to Example 1. For this purpose, composition B was fed with a throughput of 2.8 kg / h to a first extruder with a screw of 35 mm diameter and L / D of 30 with a 100-145x4 temperature profile and operating at 18 rpm, and with a throughput of 24.3 kg / h to a second extruder characterized by a screw of 40 mm diameter and L / D of 30 with a 80-145x4 temperature profile and operating at 63 rpm, and with a throughput of 2.8 kg / h to a third extruder characterized by a screw of 35 mm diameter and L / D of 30 with a 100-145x4 temperature profile and operating at 18 rpm. The coextrusion blow head had a gap of 0.9 mm and an L / D of 9 set at 145° C., delivering the monolayer construction to a film forming process operating at a blow ratio of 4.5 and a stretch ratio of 20.2. The film so obtained (total 10 microns, layer B 100%) was then mechanically and They were characterized in terms of optical properties (Table 1).
[0106] Example 4 - Two-layer film with A / B / A arrangement Preparation of Composition A (Layer A): 31.4 kg / h of poly(butylene adipate-co-butylene terephthalate) with a terephthalic acid content of 47.5 mol % based on the total dicarboxylic acid component, a MFR of 11 g / 10 min (190° C., 2.16 kg) and an acidity of 50 meq / kg, 7.6 kg / h of Ingeo 3251D polylactic acid (''PLA'') with a MFR of 58 g / 10 min (190° C., 2.16 kg), 0.8 kg / h of masterbatch containing 10 wt % Joncryl ADR4368CS (styrene-glycidyl ether-methyl methacrylate copolymer) and 90% Ingeo 4043D polylactic acid (''PLA''), 10 wt % Crodamide SR beads manufactured by Croda and 90 wt % poly(butylene adipate-co-butylene terephthalate). 0.2 kg / h of a masterbatch containing terephthalic acid was fed to an OMCEBV60 / 36 type twin screw extruder operated under the conditions specified for Layer A of Example 1. The so obtained granules had a MFR of 7.5 g / 10 min (190° C., 2.16 kg, based on ISO 1133-1 standard).
[0107] Composition A according to Example 4 and composition B according to Example 1 were fed simultaneously to a coextruder for forming a three-layer blown film with an A / B / A sequence. For this purpose, composition A was fed at a throughput of 2.9 kg / h to a first extruder with a screw with a diameter of 35 mm and a L / D of 30, with a temperature profile of 60-170x4 and operating at 11 rpm, and at a throughput of 2.9 kg / h to a second extruder characterized by a screw with a diameter of 35 mm and a L / D of 30, with a temperature profile of 60-170x4 and operating at 11 rpm. Composition B was fed at a throughput of 24.2 kg / h to an extruder with a screw with a diameter of 40 mm and a L / D of 30, with a temperature profile of 80-145x4 and operating at 64 rpm. Once melted, the two compositions were fused in a coextrusion blow head with a gap of 0.9 mm and L / D 9 set at 170° C. to feed a multilayer structure into a film forming process operating at a blow ratio of 4.5 and a stretch ratio of 20.2. The film so obtained (total 10 microns, 20% layer A, 80% layer B evenly distributed between the two layers) was then characterized in terms of mechanical and optical properties (Table 1).
[0108] Example 5 - Two-layer film with A / B / A arrangement - Preparation of composition A (layer A): 16 kg / h poly(butylene sebacic acid) with a MFR of 3.7 g / 1 min (150° C., 2.16 kg) and an acidity of 25 meq / Kg, 20 kg / h poly(butylene adipate-co-butylene terephthalic acid) with a terephthalic acid content of 47.5 mol % based on the total dicarboxylic acid content, a MFR of 5.1 g / 10 min (190° C., 2.16 kg) and an acidity of 37 meq / Kg, 4 kg / h Ingeo 4043D polylactic acid (''PLA'') with a MFR of 2.5 g / 10 min (190° C., 2.16 kg), 0.1 kg / h Crodamide ER manufactured by Croda. The microbeads were subjected to the following conditions: Screw diameter (D) = 58 mm; L / D=36; Screw rotation speed = 160 rpm; Thermal profile = 60-120-160x5-150x2℃; Throughput: 40.1kg / h; Vacuum degassing in zones 10 to 8 The mixture was fed into an OMC Model EBV60 / 36 twin screw extruder operated at 400°C. The so obtained granules had an MFR of 6 g / 10 min (190° C., 2.16 kg, according to ISO standard 1133-1 “Plastics - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard methods”).
[0109] Composition A according to Example 5 and composition B according to Example 1 were fed simultaneously to a coextruder for forming a three-layer blown film with an A / B / A sequence. For this purpose, composition A was fed at a throughput of 2.8 kg / h to an extruder with a screw with a diameter of 35 mm and a L / D of 30, with a temperature profile of 60-125x4 and operating at 11 rpm. Composition B was fed to an extruder characterized by a screw with a diameter of 40 mm and a L / D of 30, with a temperature profile of 80-145x4 and operating at 66 rpm. Once melted, the two compositions were fused in a coextrusion blow head with a gap of 0.9 mm and a L / D of 9 set at 145° C., and the multilayer structure was fed to a film-forming process operating at a blow ratio of 4.5 and a stretch ratio of 20.2. The film so obtained (total 10 microns, 20% layer A, 80% layer B) was then characterized in terms of mechanical and optical properties (Table 1).
[0110] Example 6 - Two-layer film with A / B / A arrangement Preparation of Composition A (Layer A): Poly(butylene succinic acid-co-butylene azelaic acid) having an MFR of 6 g / 10 min (190° C., 2.16 kg) and an acidity of 46 meq / kg, with an azelaic acid content of 25 mol % based on the total dicarboxylic acid content.
[0111] Composition A according to Example 6 and composition B according to Example 1 were fed simultaneously to a coextruder for forming a three-layer blown film with an A / B / A sequence. For this purpose, composition A was fed with a throughput of 2.8 kg / h to a first extruder with a screw with a diameter of 35 mm and a L / D of 30, with a temperature profile of 60-120x4 and operating at 12 rpm, and with a throughput of 2.8 kg / h to a second extruder characterized by a screw with a diameter of 35 mm and a L / D of 30, with a temperature profile of 60-120x4 and operating at 12 rpm. Composition B was fed with a throughput of 24.3 kg / h to an extruder with a screw with a diameter of 40 mm and a L / D of 30, with a temperature profile of 80-145x4 and operating at 63 rpm. Once melted, the two compositions were fused in a coextrusion blow head with a gap of 0.9 mm and L / D 9 set at 145° C. to feed a multilayer structure into a film forming process operating at a blow ratio of 4.5 and a stretch ratio of 16.8. The film so obtained (total 12 microns, 20% layer A, 80% layer B evenly distributed between the two layers) was then characterized in terms of mechanical and optical properties (Table 1).
[0112] Example 7 - Two-layer film with A / B / A arrangement Preparation of Composition A (Layer A): Poly(butylene adipate-co-butylene terephthalate) having a MFR of 3.9 g / 10 min (190° C., 2.16 kg) and an acidity of 33 meq / kg, with a terephthalic acid content of 47.5 mol % based on the total dicarboxylic acid component.
[0113] Composition A according to Example 7 and composition B according to Example 1 were fed simultaneously to a coextruder for forming a three-layer blown film with an A / B / A sequence. For this purpose, composition A was fed with a throughput of 2.8 kg / h to a first extruder with a screw with a diameter of 35 mm and a L / D of 30, operating at 16 rpm, with a temperature profile of 60-145x4, and with a throughput of 2.8 kg / h to a second extruder characterized by a screw with a diameter of 35 mm and a L / D of 30, operating at 16 rpm, with a temperature profile of 60-145x4. Composition B was fed with a throughput of 24.3 kg / h to an extruder with a screw with a diameter of 40 mm and a L / D of 30, operating at 63 rpm, with a temperature profile of 80-145x4. Once melted, the two compositions were fused in a coextrusion blow head with a gap of 0.9 mm and L / D 9 set at 145° C. to feed a multilayer structure into a film forming process operating at a blow ratio of 3.6 and a stretch ratio of 25.2. The film thus obtained (total 10 microns, layer A 20% evenly distributed between the two layers, Layer B 80%) was then characterized in terms of mechanical and optical properties (Table 1).
[0114] [Table 1]
Claims
1. A multilayer film comprising at least one first layer A and at least one second layer B, wherein the layers A and B have different compositions, and the layer A has a content of: i) 30 to 70% by weight of at least one aliphatic-aromatic polyester; ii) 20 to 60% by weight of at least one aliphatic polyester; iii) 1 to 20% by weight of at least one polyhydroxyalkanoate; iv) 0-5% by weight of at least one crosslinker and / or chain extender comprising at least one compound with bi- and / or multi-functional groups containing isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride or divinyl ether groups or mixtures thereof; v) 0-10% by weight of at least one filler; and said layer B comprises: i) 30 to 95% by weight, based on the sum of components i to v, of at least one polyester comprising: a) and b) a) a dicarboxylic acid component comprising, relative to the total dicarboxylic acid component: a1) 35 to 70 mol % of units derived from at least one aromatic dicarboxylic acid; a2) 65 to 30 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; a3) 0 to 5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid; b) A diol component which comprises, relative to the total diol component: b1) 95 to 100 mol % of units derived from at least one saturated aliphatic diol; b2) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol; ii) 0.1 to 50% by weight, based on the sum of components i to v, of at least one polymer of natural origin; iii) 1 to 40% by weight, based on the sum of components i to v, of at least one polyhydroxyalkanoate; iv) 0 to 15% by weight, based on the sum of components i to v, of at least one inorganic filler; and v) 0 to 5% by weight, based on the sum of components i to v, of at least one crosslinker and / or chain extender comprising at least one compound with bi- and / or multi-functional groups containing isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxide, anhydride or divinyl ether groups or mixtures thereof, A multilayer film comprising:
2. The aliphatic-aromatic polyester in Layer A is: c) Dicarboxylic acid components including, relative to the total dicarboxylic acid components: c1) 35 to 70 mol % of units derived from at least one aromatic dicarboxylic acid; c2) 65 to 30 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; and c3) 0 to 5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid; and d) Diol components including, relative to the total diol component: d1) 95 to 100 mol % of units derived from at least one saturated aliphatic diol, and d2) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol; The multilayer film of claim 1 , comprising:
3. The saturated aliphatic dicarboxylic acid of the component c2 is succinic acid, adipic acid, azelaic acid, sebacic acid, brassylic acid, or their C 1 ~C 24 , preferably C 1 ~C 4 3. The multilayer film of claim 2, comprising a mixture comprising at least 50 mole percent of at least one acid selected from the group consisting of esters of, and mixtures thereof.
4. 4. The multilayer film of claim 3, wherein the saturated aliphatic dicarboxylic acid of component c2 is selected from adipic acid, azelaic acid or a mixture thereof.
5. The saturated aliphatic dicarboxylic acid of the component a2 of the polyester in the layer B is succinic acid, adipic acid, azelaic acid, sebacic acid, brassylic acid, or their C 1 ~C 24 , preferably C 1 ~C 4 The multilayer film of any one of claims 1 to 4, comprising a mixture comprising at least 50 mole % of at least one acid selected from esters, and mixtures thereof.
6. 6. The multilayer film of claim 5, wherein the saturated aliphatic dicarboxylic acid of component a2 is selected from adipic acid, azelaic acid, or a mixture thereof.
7. 7. A multilayer film according to claim 1, characterized by a transmittance value greater than 90%, a haze value less than 65% and a transparency greater than or equal to 20%, measured according to standard ASTM D1003.
8. The multilayer film according to any one of claims 1 to 7, which is biodegradable under home composting conditions according to UNI 11355.
9. A packaging material comprising the multilayer film according to any one of claims 1 to 8.
10. 10. The packaging material according to claim 9, selected from bags for transporting goods and bags for packaging food.
11. 11. The bag of claim 10 for fruits and vegetables.
12. A multi-layer film comprising the multi-layer film according to any one of claims 1 to 8.
Citation Information
Patent Citations
Multilayer film having biodegradability
JP2012076443A
Biodegradable polyester film
JP2014523962A
Multilayer film
JP2015536255A
Biodegradable Packaging Film
US20090324917A1
Polymer mixture for barrier film
WO2015086463A1